AN OBSERVATIONAL STUDY OF DRUG USE IN UPPER RESPIRATORY TRACT INFECTION IN PATIENTS ATTENDING ENT OPD IN A TERTIARY CARE HOSPITAL IN KOLKATA - Ghosh, Arcojit; Das, Asoke Kumar; K Gure, Prasanta; Pati, Sampurna (Asian Journal of Pharmaceutical and Clinical Research, 2015)
CONTEXT: Majority of upper respiratory tract infections are caused by viruses & thus are self limiting. However, irrational prescription of drugs including antibiotics for URTI is a major problem worldwide. Thus, it is imperative to monitor drug utilization patterns from time to time in order to suitably modify prescribing patterns. AIMS: To evaluate the drug prescribing pattern in symptomatic upper respiratory tract infections in patients attending ENT OPD in R G Kar Medical College & Hospital, Kolkata. SETTINGS & DESIGN: A prospective study based on a Medication Utilization Form, designed on the basis of WHO format. METHODS & MATERIAL: The study was conducted in ENT OPD. The study population comprised of all patients with symptomatic URTI attending ENT OPD, RGKMCH. The data were obtained from the prescribing records. STATISTICAL ANALYSIS USED: Descriptive type. RESULTS: A total of 300 prescriptions were audited. It was found that 63.66% were males, 24.66% belonged to the age group of 26-35 yrs followed by 20.66% belonging to the age group of 16-25 yrs. The three most common URTIs diagnosed were otitis media(41%), pharyngitis (30%) & tonsillitis(12%). 594 drugs in total were prescribed to 300 patients (1.98 drugs per prescription). Among them 60% were generic prescriptions. Antibiotics were prescribed to 74% of patients. Average duration of treatment was 5-7 days. The most frequently prescribed antibiotic was amoxicillin & clavulinic acid (45%) followed by azithromycin (22%). Paracetamol accounted for majority of analgesic/ antipyretic prescriptions (57%). Antihistaminics were prescribed in 37% of cases. Nasal decongestants were prescribed to 14% patients & mucolytics to 7%. CONCLUSION: The study revealed lesser utilization of antibiotics, better percentage of generic prescriptions & duration of antibiotic therapy in comparison to similar studies. Keywords: Upper respiratory tract infection, prescribing pattern, antibiotics.